Delta Neutrophil Index as a Promising Biomarker for Placental Implantation Disorders - Karakoç, Gökhan; Yalcin, Serenat Eris; Yavuz, And; Sarsmaz, Kemal; Şengül, Mustafa; Yucel, Aykan (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Objective We aimed to investigate the value of maternal serum delta neutrophil index (DNI) levels in predicting placenta accreta spectrum in patients with placenta previa.Methods The patients who were found to have placenta previa totalis were included in our study. Location of placental implantation and depth of myometrial invasion were defined by transabdominal and transvaginal 2D gray scale and Doppler sonography and confirmed during cesarean section and histopathological evaluation. Patients were subjected to complete blood counts, including prenatal hemoglobin level, total white blood cell count, differential leukocyte count, and platelet count. The following formula was used to calculate the DNI level: DNI (%)=(leukocyte subfraction analyzed by cytochemical reaction in the MPO channel) - (leukocyte subfraction analyzed using the nuclear lobularity channel with reflected light beam measurements).Results Placenta previa was detected in 295 patients; 31 of them had PAS. As the control group, 189 patients were evaluated. In the group with PAS, the DNI value was significantly higher (p<0.05) than the other groups. DNI value in the group with previa only was also significantly higher (p<0.05) than the control group. In the univariate model, a significant (p<0.05) effect of DNI value and number of cesarean sections was observed in separating patients with previa only and PAS. In the multivariate model, a significant independent (p>0.05) effect of the DNI value was observed in separating patients with previa only and PAS. Significant efficiency of DNI value [area under the curve 0.899 (0.814–0.984)] was observed in differentiating patients with previa only and PAS. Significant efficacy of DNI 5 cut-off value [area under the curve 0.858 (0.770–0.946)] was observed in distinguishing patients with previa only and PAS (sensitivity 80.0%, positive predictive value 64.9%, specificity 91.6%, negative predictive value 95.9%)Conclusion Maternal DNI values seem to be beneficial with respect to both previa and invasion prediction. Although more comprehensive studies are needed to test this proposition, prediction studies of this practical test should be done in different trimesters and its usability with respect to preventing maternal-fetal morbidity should be investigated.
Keywords: delta neutrophil index; placenta accreata spectrum; placenta previa